Synergy of Educational, Digital, and Repressive Strategies in Traffic Governance: A Study of the Subdirectorate of Traffic Violation Enforcement of the Indonesian National Police Traffic Corps - Theodora, Cannysia Sherryl; Wijaya, Komang Adi Sastra (Jurnal Manajemen Pelayanan Publik, 2026)
This study examines the synergy between educational, digital, and repressive strategies implemented by the Subdirectorate of Traffic Violation Enforcement of the Indonesian National Police Traffic Corps (Korlantas Polri) in enhancing the effectiveness of traffic law enforcement in Indonesia. Employing a descriptive qualitative approach, data were collected through semi-structured interviews, participatory observation, and analysis of ETLE (Electronic Traffic Law Enforcement) reports. The findings indicate that the three strategies operate as an interdependent system: educational initiatives function as a moral and preventive foundation, digital mechanisms improve transparency and accountability, and repressive measures ensure immediate compliance with traffic regulations. Empirical ETLE data from 2022–2024 revealed a 17.3% reduction in traffic violations during the first semester following digital implementation, indicating measurable behavioral change. However, this impact appears to be temporary and requires sustained inter-institutional coordination to remain effective. The study concludes that successful traffic governance depends on the continuous synergy between education, digitalization, and fair law enforcement, supported by strong institutional capacity and active public participation.